VEGF Modulates Neurogenesis and Microvascular Remodeling in Epileptogenesis After Status Epilepticus in Immature Rats - Han, Wei; Jiang, Li; Song, Xiaojie; Li, Tianyi; Chen, Hengsheng; Cheng, Li (Frontiers in Neurology, 2021)
Neurogenesis and angiogenesis are widely recognized to occur during epileptogenesis and important in brain development. Because vascular endothelial growth factor (VEGF) is a critical neurovascular target in neurological diseases, its effect on neurogenesis, microvascular remodeling and epileptogenesis in the immature brain after lithium-pilocarpine-induced status epilepticus (SE) was investigated. The dynamic changes in and the correlation between hippocampal neurogenesis and microvascular remodeling after SE and the influence of VEGF or SU5416 injection into the lateral ventricles at different stages after SE on neurogenesis and microvascular remodeling through regulation of VEGF expression were assessed by immunofluorescence and immunohistochemistry. Western blot analysis revealed that the VEGFR2 signaling pathway promotes phosphorylated ERK and phosphorylated Akt expression. The effects of VEGF expression regulation at different stages after SE on pathological changes in hippocampal structure and spontaneous recurrent seizures (SRSs) were evaluated by Nissl staining and electroencephalography (EEG). The results showed that hippocampal neurogenesis after SE is related to microvascular regeneration. VEGF promotion in the acute period and inhibition in the latent period after SE alleviates loss of hippocampal neuron, abnormal vascular regeneration and inhibits neural stem cells (NSCs) ectopic migration, which may effectively alleviate SRS severity. Interfering with VEGF via the AKT and ERK pathways in different phases after SE may be a promising strategy for treating and preventing epilepsy in children.